PENGARUH PENGADOPSIAN INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) TERHADAP MANAJEMEN LABA - Ayem, Sri; Wahidah, Umi (Optimum: Jurnal Ekonomi dan Pembangunan, 2018)
This research aimed to examine the effect of the adoption of International Financial Reporting Standards (IFRS) on eearning management on companies listed in IDX. Earning management that used in this research was discretionary accrual. This research is also use the control variable size, leverage, and return on equity (ROE). This research used populations sector of transport service companies that listed in Indonesia Stock Exchange. The data of this research taken from secondary data that was from the Indonesia Stock Exchange in the form of Indonesian Capital Market Directory (ICMD) and the annual report of the company 2011-2015. The method of collecting sample was purposive sampling technique as many as 75 companies. The method of analysis used in this research is multiple regression analysis. Based on regression testing shows that the adoption of International Financial Reporting Standards (IFRS) have a negative significant effect on earnings management. This indicates that the adoption of IFRS can decrease earnings management practices. ROE control variables also significantly affect the application of IFRS in the practice of earnings management, while control size and leverage variables do not affect the application of IFRS in practice earnings managementÂ